A 2 × 1 array‐based wideband mm‐wave antenna integrated with a 2‐element multiple‐input‐multiple‐output antenna for 5G mobile terminals. Issue 8 (21st April 2021) - Salamin, Mohammad Ahmad; Hussain, Niamat; Le, Tuan Tu
Abstract: A novel wideband millimeter (mm)‐wave antenna integrated with a multi‐input multi‐output (MIMO) antenna is presented for fifth‐generation (5G) applications. The proposed model consists of a 2 × 1 array‐based single‐element wideband antenna for mm‐wave applications, and a 2‐element strip‐based MIMO antenna system for sub‐6‐GHz band applications. In the ground plane, two clearance regions were etched to improve the impedance matching of MIMO elements while an open‐circuit rectangular tuning stub is attached to the mm‐wave antenna feed line to broaden its impedance bandwidth. The dimensions of the used panel are 100 × 60 × 0.8 mm 3, which are among the typical dimensions used in mobile terminals. The mm wave antenna covers the frequency ranges from 25.08 to 28.08 GHz, while the frequencies from 2.88 to 4.58 GHz and from 5.15 to 6.15 GHz are covered by the MIMO antenna. Depending on the experimental results achieved, the suggested design might be considered a successful candidate for 5G applications, with wideband characteristics, excellent field correlation, and high gain functionality.